PRODUKTIVITAS TERNAK BABI DAN PERANANNYA DALAM PEMBERDAYAAN MASYARAKAT ASLI PAPUA DI KABUPATEN MANOKWARI - , HIERONYMUS YOHANES CHRYSOSTOMUS; , Ir. I Gede Suparta Budisatria, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to investigate the productivity of pigs kept by indigenous Papuans, their role in local community life, identify problems and solutions that can be taken, and develop the right strategy for the empowerment of indigenous Papuans can be done through increased productivity of pigs in Manokwari. This research was conducted in Minyambouw and Kebar District, using survey methods, purposive sampling was conducted, and the data were analyzed descriptively. Respondents taken as many as 31 people, which maintains 106 pigs. Sows maintained have a productivity as follows: the number of farrowing rate once/year of 22.5% and two times/year 77.5% of the born and weaned litter size on litter first and second respectively in the amount of 5.88Â±1.80 and 6.92 Â± 1.95. Sows with farrowing rate one time/year produce piglet by 60 head (10.9%), while sows with farrowing rate twice/year produce as many piglet as 486 head (89.1%). Pigs generally maintained contribute to fulfill the needs of families. The conclusion of this research is the productivity of pigs are kept low